Preparation and In-vitro Degradation Behavior of Poly(L-lactide-co-glycolide-co-ε-caprolactone) Terpolymer. Issue 5 (4th May 2019) - Wu, Wei; Zhou, Zhihua; Liu, Wenjuan; Zhao, Yunhui; Zhao, Yanmin; Huang, Tianlong; Li, Xiaofei; Fang, Jianjun
Abstract: A random terpolymer of poly(L-lactide-co-glycolide-co-ε-caprolactone) (PLLGC) was synthesized from L-lactide, glycolide and ε-caprolactone. The in-vitro hydrolytic degradation behavior of the PLLGC terpolymer was investigated as a function of the degradation time; the results showed that the degradation rate of PLLGC was lower than that of PLGA due to a reduction in the acidic degradation products. Therefore, we suggest the degradation rate of the PLGA could be controllable by introduction of ε-caprolactone into the PLGA martrix, while the physical properties (mechanical, etc.) were superior to PLGA.